Scientists Trained to Model Climate-Smart Solutions for Mixed Farming Systems - Kumar, Shalander; Jat, Mangi Lal; Pramanik, Soumitra (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Hyderabad, 7 December 2024—Twenty-three agricultural scientists from six countries in Asia and Africa participated in a hands-on workshop to enhance their skills in using modern modeling tools. The aim was to build participants' capacity to analyze the complexities of mixed farming systems and devise sustainable solutions.